Ebulição nucleada em placa plana com geração transiente de calor - Bastos, Leopoldo Eurico Gonçalves (1975)
ln a flat platinum ribbon immersed in saturated pool water at atmospheric pressure, power is uniformly generated at a linearly increasin'g rate with durations of 191, 25ms and 200ms. The variation with time of the ribbon temperature, power generated and energy release rate transfered to the liquid, are experimentally determined. The method applied in the experiments follows the resistance thermometry principle, and the dynamic control is made with the aid of a closed loop system using the hybrid computer EAI-TR48, DES-30. To explain the phenomenon, a theoretical model for the heat transfer mechanism is proposed which considers the preboiling and the nucleate boiling regimes. The model assumes a uniform spacial distribution for the bubbles which grow on the flat surface and a saturation density for the number of bubbles on the surface.